Al-Taḥāwulāt al-Jadīdah fi Ta’līm al-Lugah al-'Arabiyyah li al-Nāṭiqīna bi Gairiha fi al-Mustawa al-Jāmi’ī - Uril Bahruddin; Sutaman Sutaman; Syuhadak Syuhadak (Jurnal Alsinatuna, 2021)
The aim of Arabic learning for the Indonesian people is not only to understand religion. In fact, Arabic learning has undergone a change in orientation towards a more perfect direction. The purpose of this article is to understand (1) the orientation of Arabic learning in tertiary institutions, (2) models of transformation of Arabic learning in higher education based on a new orientation of Arabic learning. So far this aspect has not been paid attention to in existing studies. This study uses a qualitative approach with a descriptive analysis model. Data collection was carried out through interviews, observation and documentation. Data were analyzed from the start of data collection, then data description and data reduction, then verification in detail. The results of this study indicate that there is a change in orientation in learning Arabic in Indonesian universities, which previously only oriented maharah qira'ah to understand religious texts, to become perfectly oriented to master the four language skills. A new transformation model is being carried out by several universities that teach Arabic, characterized by intensive learning using a modern curriculum and the availability of an appropriate language environment. In conclusion, it turns out that learning Arabic in Indonesia leads to a better direction if it is consistent with a new orientation and follows the development of language learning in other worlds.